Obstacles and Opportunities Of Implementing Asta Ethics Librarians In Library Information Services In Indonesia - Yehuda Abiel; Anis Masruri (Universitas Airlangga, 2023)
ABSTRACT Ethics itself is very closely related to human existence as individuals in society. In society, harmonious coexistence of individuals cannot be separated from ethics that are able to harmonize existing differences. Ethics is also regulated in every religion. All religions teach three main things in their holy books, namely the nature of God, ethics/morality, and rituals/worship. There is no religion that does not teach ethics. The higher the faith, the better the morals. The Librarian Code of Ethics is a starting point for librarians in carrying out their duties, in which there are guidelines for behavior that can be used to avoid unprofessional behavior. This research was conducted using descriptive qualitative research methods supported by literature studies. As many as 6 of the 7 librarians interviewed admitted that they had never heard of Asta Librarian Ethics, while 1 librarian stated that they had heard of Asta Ethics for Librarians, and this shows that this code of ethics is not very popular among librarians. IPI itself has a crucial role in the development of librarianship in Indonesia and the application of an even code of ethics to librarians in Indonesia which is oriented towards excellent service to and satisfaction of users and society in general. Keywords: Ethics, librarian, organization, indonesia. OBSTACLES AND OPPORTUNITIES OF IMPLEMENTING ASTA ETHICS LIBRARIANS IN LIBRARY INFORMATION SERVICES IN INDONESIA ABSTRAK Etika sendiri sangat erat kaitannya dengan eksistensi manusia sebagai individu yang hidup di tengah-tengah masyarakat. Keharmonisan interaksi antar-individu dalam masyarakat tidak lepas dari etika yang sanggup menyelaraskan perbedaan yang terjadi. Etika pun juga diatur dalam setiap agama. Menurut Agoes (2011) semua agama mengajarkan melalui kitab sucinya tiga hal pokok yaitu hakikat Tuhan, etika/tata susila dan ritual/tata cara beribadah. Tidak ada agama yang tidak mengajarkan etika. Semakin tinggi keimanan seseorang seharusnya menjadi semakin baik etika yang dimilikinya. Kode Etik Pustakawan merupakan pijakan awal bagi para pustakawan dalam melaksanakan tugasnya di tempat ia bekerja, yang di dalamnya memberikan pedoman tingkah laku yang dapat menghindarkan diri dari tindakan yang tidak professional. Penelitian ini dilakukan menggunakan metode penelitian kualitatif deskriptif yang didukung dengan studi literatur. Penulis mencoba mewawancari 7 pustakawan dari 3 perpustakaan perguruan tinggi di Indonesia dan 6 dari 7 pustakawan tersebut mengaku belum pernah sekalipun mendengar tentang Asta Etika Pustakawan. IPI sendiri memiliki peranan krusial dalam perkembangan kepustakawanan di Indonesia dan penerapan kode etik yang merata kepada pustakawan di Indonesia yang berorientasi kepada layanan prima kepada dan kepuasan pemustaka serta masyaarakat pada umumnya. Keywords: Etika, pustakawan, organisasi, indonesia